"I Will Not Be Defined by This. I'm Not Going to Live Like a Victim; It Is Not Going to Define My Life": Exploring Breast Cancer Survivors' Experiences and Sense of Self. (January 2021) - Rashidi, Elly; Morda, Romana; Karnilowicz, Wally
A life-threatening disease such as breast cancer with its pervasive nature of uncertainty can lead to feelings of disempowerment. Nonetheless, survivors may reconstruct their identity within optimism and a celebration of a new self. In this qualitative constructionist study, we explored survivors' experiences, meaning-making, and identity transformation. Semi-structured interviews were undertaken with 11 women who identified as breast cancer survivors. Participants were aged 35 years old or above and were in post-diagnosis for at least 3 years. Interview data were collected and analyzed using thematic techniques. We identified three master themes: Diseased Self, focused on emotional distress and the presentation of a façade; Coping Self, explored resilience and post-traumatic growth; and Transformed Self, engaged in presentations of self-image, meaning-making, and psychological ownership addressing survivorship and empowerment. The findings may be used to inform guidelines and support for cancer survivors considering the impact of diagnosis, treatment, and post-treatment experiences on self-identity.